I am not sleepy and I will not go to bed - Child, Lauren (Cambridge, Mass. : Candlewick, 2005)
Charlie helps Lola get ready for bed, despite the tigers, whales, and other animals that serve as obstacles.
Booklist.
Pub Weekly.
School Library Journal.
2.6
K-3
Keywords: Animals -- Juvenile fiction; Bedtime -- Juvenile fiction; Animals -- Fiction; Bedtime -- Fiction; Humorous stories; Animals -- Fiction; Bedtime -- Fiction; Humorous fiction